2014
DOI: 10.3846/16486897.2013.911182
|View full text |Cite
|
Sign up to set email alerts
|

Testing of Chlorella/Scenedesmus Microalgae Consortia for Remediation of Wastewater, Co₂ Mitigation and Algae Biomass Feasibility for Lipid Production

Abstract: Industry, transport and unsustainable agriculture result in the increased quantity of wastewater, release of nutrients and emission of carbon dioxide that promotes eutrophication of water bodies and global climate change. the application of microalgae for phycoremediation, their biomass use for human needs may increase sustainability and have a positive effect on the regional development. The experiments were carried out in order to establish the feasibility of treating the local municipal wastewater with micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…The selection of the appropriate micro-algae species and appropriate methods of culture is essential to guarantee the economic feasibility of the intensive production of micro-algae. Chlorella and Scenedesmus have been considered promising candidates for wastewater treatment ( [2,3]) and bio-fuel production ( [2,4,5]), thanks to their maximum growth rates, biomass yields, and lipid and carbohydrate contents, which can reach high levels.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of the appropriate micro-algae species and appropriate methods of culture is essential to guarantee the economic feasibility of the intensive production of micro-algae. Chlorella and Scenedesmus have been considered promising candidates for wastewater treatment ( [2,3]) and bio-fuel production ( [2,4,5]), thanks to their maximum growth rates, biomass yields, and lipid and carbohydrate contents, which can reach high levels.…”
Section: Introductionmentioning
confidence: 99%
“…for the treatment of raw wastewater from effluents of the tannery industry for nutrients removal 11,12 . Furthermore, studies show that microalgae consortium is more efficient in the removal of pollutants and nutrients, like nitrogen, phosphorus, and ammonium, from wastewater when compared to individual microorganisms applied for the treatment local municipal wastewater 13 and dairy farm 14 . In this context, investigations about the isolation of the microalgae species present in the consortium in the environment are searched.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, several studies have reported the advantages of co-cultivated photosynthetic microorganisms in WW treatment. On the one hand, Koreivienè et al (Koreivienė et al, 2014) reported high nutrient removal efficiencies in municipal WW treatment using a non-native consortium composed of Chlorella sp. and Scenedesmus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Renuka et al (Renuka et al, 2013) described the selfflocculating potential of native and non-native consortia in the treatment of a primarytreated sewage effluent. Among the possible combinations of microalgae, many consortia involve Chlorella and Scenedesmus species (Koreivienė et al, 2014;Renuka et al, 2013;Whitton et al, 2016). Moreover, few woks have been carried out in order to study the biodegradadion of 17β-estradiol at pilot-plant photobioreactor, and in this study the capability of native photobioreactor biomass treating urban wastewater to remove at indoor and outdoor conditions has been assessed.…”
Section: Introductionmentioning
confidence: 99%